Proficiency testing for HIV, tuberculosis and malaria diagnosis in clinical laboratories in Nigeria - Rosemary A. Audu; Catherine C. Onubogu; Rosemary N. Okoye; Nkiru N. Nwokoye; Chika K. Onwuamah; Adesola Z. Musa; Toyosi Y. Raheem; Maureen N. Aniedobe; Samuel J. Nduaga; Ini-Obong Essien; Emmanuel O. Idigbe (AOSIS, 2014)
Background: Proficiency testing (PT) is a means of verifying the reliability of laboratory results, but such programmes are not readily available to laboratories in developing countries. This project provided PT to laboratories in Nigeria. Objectives: To assess the proficiency of laboratories in the diagnosis of HIV, tuberculosis and malaria. Methods: This was a prospective study carried out between 2009 and 2011. A structured questionnaire was administered to 106 randomly-selected laboratories. Forty-four indicated their interest in participation and were enrolled. Four rounds of pre-characterised plasma panels for HIV, sputum films for tuberculosis and blood films for malaria were distributed quarterly by courier over the course of one year. The results were returned within two weeks and scores of ≥ 80% were reported as satisfactory. Mentoring was offered after the first and second PT rounds. Results: Average HIV PT scores increased from 74% to 95% from the first round to the third round, but decreased in the fourth round. For diagnosis of tuberculosis, average scores increased from 42% in the first round to 78% in the second round; but a decrease to 34% was observed in the fourth round. Malaria PT performance was 2% at first, but average scores increased between the second and fourth rounds, culminating in a fourth-round score of 39%. Many participants requested training and mentoring. Conclusions: There were gross deficiencies in the quality of laboratory services rendered across Nigeria. In-country PT programmes, implemented in conjunction with mentoring, will improve coverage and diagnosis of HIV, tuberculosis and malaria.